Mitigating board endorsement through re-spinning with surface-mounted device under test pad - Ber-Riel Malimban; Glenn N. Ortiz; Mark Joseph B. Enojas (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The two-part legacy board device under test (DUT) pad has been very useful for testing of microelectronic packages. However, this board has been subjected to many repair endorsements due to open connection of DUT pad and cut traces of the board components as recorded. Board re-spin is used to improve the performance of the test boards in microelectronic packages production. It improves the board development to create more functional printed circuit boards for testing and introduces the use of modern tools and software applied to the schematic creation up to the production board debugging. This paper presents a method of creating test boards for the development and manufacturing of microelectronic packages and integrated circuits. The two-part board is converted into a single board interface which eliminates the open DUT connections. A surface-mounted DUT pad is introduced to replace the old hypertact pins which are included in the re-spin board for a more robust performance. The schematic creation and board debugging were done to lessen problems caused by connection faults. In result, producing re-spin boards mitigates board endorsement which in return increases the manufacturing output performance. A faster and convenient setup was achieved when the old two-board setup was eliminated.